Serum LDL Cholesterol/HDL Cholesterol Ratio Alternative to Albumin in Relation to Coronary Heart Disease (Journal of Medicine, 2008)
In a study of coronary heart disease in males, their is a correlation between LDL cholesterol/ HDL cholesterol ratio & albumin(r= 0.46,p < 0.001).We then correlated the LDL cholesterol: albumin ratio( TC: Alb) with the LDL c : HDL -c ratio ( r= 0.12,p < 0.001).An excellent correlation was obtained between LDL-C : Alb ratio separated the patients with normal ( < 5) and increased (>5) LDL-C: HDL-C ratio better than LDL-C by itself(Amin A Nanji, Suseela Reddy et al). Â Â  DOI = 10.3329/jom.v7i2.1364 J MEDICINE 2006; 7 : 51-53